2014
DOI: 10.1515/jpem-2013-0161
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in young patients with galactose metabolic disorders: a preliminary report

Abstract: An imbalance between muscle and fat mass, especially in patients with classic galactosemia, was observed. Given the observed strong correlation between bone and muscle mass, more effective lifestyle counseling is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…At the site of the lumbar spine, a mean BMD Z-score of À0.70 (95% CI: À0.88, À0.52) was found (Panis et al 2004;Waisbren et al 2012;Tan et al 2014;Doulgeraki et al 2014). Heterogeneity was zero (I 2 ¼ 0%); a fixed effects model was used.…”
Section: Complete Cohort (Children and Adults)mentioning
confidence: 96%
See 3 more Smart Citations
“…At the site of the lumbar spine, a mean BMD Z-score of À0.70 (95% CI: À0.88, À0.52) was found (Panis et al 2004;Waisbren et al 2012;Tan et al 2014;Doulgeraki et al 2014). Heterogeneity was zero (I 2 ¼ 0%); a fixed effects model was used.…”
Section: Complete Cohort (Children and Adults)mentioning
confidence: 96%
“…Only one of these studies reported all data required for inclusion (Panis et al 2004); the authors of the other seven studies were contacted for additional information. Three authors provided the required data at request (Waisbren et al 2012;Tan et al 2014;Doulgeraki et al 2014) (Supplementary data S3, Data collection process). Accordingly, a total of four articles were included in our meta-analysis on BMD.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased bone mineral density has been consistently observed in galactosaemia patients (Rubio-Gozalbo et al 2002;Panis et al 2004;Waisbren et al 2012;Batey et al 2013;Coss et al 2013;Doulgeraki et al 2014). Decreased bone metabolism has been suggested as the mechanism of reduced bone mineral density in galactosaemia as well as abnormal galactosylation of the collagen matrix (Kaufman et al 1993).…”
Section: Congenital Disorders Of Glycosylationmentioning
confidence: 99%